Study on the mechanism of BGN in progression and metastasis of ccRCC - Hanqing Xia; Tianzhen He; Xueyu Li; Kai Zhao; Zongliang Zhang; Guanqun Zhu; Han Yang; Xuechuan Yan; Qinglei Wang; Zhaofeng Li; Zaiqing Jiang; Ke Wang; et al. (BMC Medical Genomics)
Abstract Purpose To investigate the role of Biglycan(BGN) in the progression and metastasis of clear cell renal cell carcinoma(ccRCC). Methods Based on multiple public databases, we investigated the expression level of BGN in ccRCC, its clinical significance, and its association with immune cells. Real-time fluorescence quantitative polymerase chain reaction(PCR) was employed to validate BGN expression in tumor and adjacent normal tissues from ten patients. We utilized RNA sequencing results for further analysis, including differential gene analysis, GO-KEGG analysis, and GSEA analysis, to identify the signaling pathways through which BGN exerts its effects. BGN knockdown cells(786–0 and Caki-1) were generated through lentiviral transfection to examine the impact of BGN on ccRCC. Cell proliferation, migration, and invasion were assessed using CCK8, colony formation, wound healing, Transwell migration, and invasion assays, respectively. Results Our findings from database analysis and PCR revealed a significant upregulation of BGN expression in kidney cancer tissues compared to normal tissues. Further analysis demonstrated a correlation between high BGN expression and ccRCC progression and immune infiltration. In vitro experiments confirmed that BGN silencing effectively inhibited cell proliferation, migration, and invasion of ccRCC. Mechanistically, these effects may be mediated through the MAPK signaling pathway. Conclusion BGN potentially plays a pivotal role in the progression and metastasis of ccRCC, possibly acting through the MAPK signaling pathway. Therefore, BGN holds promise as a potential therapeutic target for ccRCC.